Polychlorinated Alkanes in Fish from Norwegian Freshwater - Anders R. Borgen; Martin Schlabach; Roland Kallenborn; Eirik Fjeld (The Scientific World Journal)
Short-chain polychlorinated alkanes (sPCAs) have been measured in freshwater fish samples from different lakes all over Norway and from the Norwegian Arctic. The analyses were performed with high-resolution GC coupled to high-resolution MS in electron capture negative ion mode. The species investigated were trout, Arctic char, and burbot (Lota lota). Muscle tissue in the lake trout and Arctic char, and liver in burbot, were selected for analyses because of their high lipid content. ∑sPCA concentration ranged from 108 to 3700 ng/g fat. The highest value was found in the south of Norway near an industrial area.